Pendampingan dan pelatihan pembuatan PGPR kepada petani tanaman hortikultura di kampung Kwau : Guidance and training in PGPR production for farmers in Kwau village - Ruimassa, Reymas; Ayuningtias, Nandini; Pribadi, Hayu S.P.; Nurlailah, Nurlailah (Fakultas Peternakan Universitas Papua, 2026)
ABSTRACT Plant pests and diseases threaten horticultural production in Kwau, where farmers often rely on synthetic pesticides without adequate understanding of safe use, human and environmental risks, or pesticide resistance. This community engagement introduced plant growth promoting rhizobacteria (PGPR) as a biological approach to plant pest organisms, using local materials to lower cost and reduce travel to Manokwari for chemical purchases. Sessions at the Kwau village hall and a demonstration in a farmer’s garden delivered plain-language guidance on PGPR concepts, simple production, and safe application. Farmers participated actively and responded enthusiastically, indicating greater awareness of biological control and a practical entry point for using PGPR. Lasting benefits will depend on structured follow-up with farmers and local institutions. Keywords: Kwau; Mentoring; Organic; Plant disease; Rhizobacteria ABSTRAK Hama dan penyakit tanaman mengancam usahatani hortikultura di Kampung Kwau; petani banyak memakai pestisida sintetis tanpa pemahaman memadai tentang pemakaian aman, risiko kesehatan dan lingkungan, serta resistensi. Pengabdian ini memperkenalkan Plant Growth Promoting Rhizobacteria (PGPR) sebagai alternatif hayati pengendalian Organisme Pengganggu Tumbuhan memakai bahan lokal guna menekan biaya dan ketergantungan pada pembelian pestisida kimia di Manokwari. Pelatihan di Balai Kampung Kwau dilanjutkan demonstrasi di kebun petani dengan penyampaian bahasa sehari-hari tentang konsep PGPR, pembuatan sederhana, dan aplikasi aman. Peserta antusias dan aktif, menandakan peningkatan kesadaran pengendalian hayati dan titik awal praktik PGPR. Manfaat berkelanjutan bergantung pada pendampingan lanjutan bersama mitra setempat. Kata kunci: Kwau; Organik; Pendampingan; Penyakit tanaman; Rhizobacteria